Peta Distribusi Sebaran Kualitas Fisik Air di Danau Sipin Kota Jambi dan Rekomendasi Pemanfaatannya - Adrian Lutfi Raedjani; M Syarif; Moch Zuhdi (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to determine the water quality in Lake Sipin based on the physical quality of the water, to provide information on the distribution map of the distribution of water quality based on the physical quality of the water and to examine the allotment for the management of Lake Sipin. Lake Sipin water is one of the water sources used by the community for daily life. The quality of water in aquaculture activities is influenced by the life of the surrounding environment. Water quality has different quality standards for each designation, so it is important to monitor and evaluate water quality. The data collection technique was carried out by purposive sampling using the Storet method and the Stepwise test was carried out. The parameters observed in this study were temperature, TDS, TSS, turbidity and pH. Based on the results of the study, it was found that the quality standards for each parameter were included in the second class water quality standard. Calculation using the Storet method, water quality gets a value of -4, meaning that the water quality of Lake Sipin is in a lightly polluted status. The relationship between parameters that have a relationship from the results of the stepwise test. TSS and TDS have a relationship with the value of R = 0.661 with the assumption that the higher the TSS value, the lower the TDS value. Turbidity and TSS have a relationship with the value of R = 0.731 with the assumption that the greater the value of Turbidity, the greater the TSS value. pH and TDS have a relationship with the value of R = 0.518 with the assumption that the smaller the pH value, the greater the TDS value. The status of the water quality in Lake Sipin meets the water quality standards, meaning that the water quality in Lake Sipin is still good. The water quality distribution map has various distributions and the water in Sipin Lake can still be used according to the second class water classification based on observations of water physics parameters.